1992
DOI: 10.1056/nejm199201023260104
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reduced Suppression of Glucose Production and Diminished Early Insulin Release in Impaired Glucose Tolerance

Abstract: Impaired glucose tolerance, the precursor of NIDDM, results primarily from reduced suppression of hepatic glucose output due to abnormal pancreatic islet-cell function. The late hyperinsulinemia may be the consequence of an inadequate early beta-cell response rather than of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
398
5
14

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(446 citation statements)
references
References 47 publications
29
398
5
14
Order By: Relevance
“…However, impaired pancreatic beta cell function is an essential element in the development of abnormal glucose tolerance. Indeed, altered beta cell function is a known predisposing factor for type 2 diabetes [4][5][6][7][8], while other studies have found that insulin insensitivity and abnormal beta cell function are independent predictors [9][10][11]. A major problem until now has been the lack of detailed information about the specific abnormalities of beta cell function that predispose to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, impaired pancreatic beta cell function is an essential element in the development of abnormal glucose tolerance. Indeed, altered beta cell function is a known predisposing factor for type 2 diabetes [4][5][6][7][8], while other studies have found that insulin insensitivity and abnormal beta cell function are independent predictors [9][10][11]. A major problem until now has been the lack of detailed information about the specific abnormalities of beta cell function that predispose to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the manifestations of alpha cell dysfunction described above have been reported in subjects with IGT [6,43,44]. Furthermore, a prospective study of postmenopausal women found that the AGR arg at a clamped plasma glucose of 14 mmol/l was an independent predictor of glucose intolerance [45].…”
Section: Abnormalities Of Alpha Cell Function In Diabetesmentioning
confidence: 92%
“…Impaired suppression of glucagon release can be detected in individuals with impaired glucose tolerance (IGT) and type 2 diabetes following intravenous [2] or oral glucose administration [3]. Fasting glucagon concentrations exert a tonic stimulatory influence on hepatic glucose output, which in the dog has been estimated to account for one-third of the fasting rate of glucose release [4].…”
Section: Introductionmentioning
confidence: 99%